Climate-smart technology adoption in hazard-prone areas: does this adoption impact farm families’ food security? - Jinyu Qian; Airin Rahman; Naiping Zhu; Mohamad Alnafissa (Humanities & Social Sciences Communications)
Abstract Before evolving an effective plan to support farmers on a large-scale regarding climate risk management, it is crucial to understand climate risk, risk adaptation, and its possible impacts at the local farm level in a country like Bangladesh where the food security facing massive threat due to climate related vulnerability. This study aims to explore the factors influencing the decision of climate-smart technology adoption choices and its effects on household food security. We gathered data from 600 participants and assessed their impacts on all the dimensions of food security. We have used multivariate probit, multiple regression and propensity score matching (PSM) to identify the influential factors and their impacts. The PSM results show that farmers who adopted saline tolerant variety as climate-smart strategy are enjoying more calorie intake (2%), food stock availability (1 meal more) and food expenses can be borne for next 1–1.5 months, than the farmers who did not adopted any strategy. Farmers who adopted crop shifting to minor crops showed a 3% - 4% increase in calorie intake. For them meal/day increased by 2–3meal/day and food purchase power also increased (cash in hand up to next 3 months for food purchase) than the control group. In terms of adopting sowing time adjustment, the results are even more pronounced and the food purchase power increased up to next 6 months for this group. This was unquestionably stable food secure situation for this peripheral group of farmers. The government and policymakers need to develop a proper plan to disseminate knowledge of technology and facilities so that poor farmers can fairly access them. This knowledge could aid national policy focused on implementation of sustainable cultivation practices with proper knowledge dissemination to counter climatic challenges. It also helps shaping government investment decisions to bolster specific sectors of rice farming in hazard-prone areas at any corner of the country.